ORGANIZE ADDITIONAL CLEANING BY IMPROVING THE DESIGN OF THE PNEUMATIC CONVEYING DEVICE - Jumanyozova Irodaxon Olimboy kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation - This article puts forward scientific and technical ideas for organizing additional cleaning by improving the design of the pneumotransport device.